2011
DOI: 10.1097/rlu.0b013e318203bb84
|View full text |Cite
|
Sign up to set email alerts
|

Undetectable Thyroglobulin in Patients With Differentiated Thyroid Carcinoma and Residual Radioiodine Uptake on a Postablation Whole-Body Scan

Abstract: A careful assessment of interferences in Tg measurement significantly reduced the occurrence of undetectable Tg among patients with ¹³¹I uptake in PT-WBS. However, such extensive assessment is difficult in clinical practice and one-fifth of patients still had undetectable Tg in multiple assays despite an intensive laboratory work-up. A benchmark between ¹³¹I imaging and Tg measurement authenticates the interpretation of Tg measurements and, consequently, remains of pivotal value by authenticating the use of se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 20 publications
1
29
0
Order By: Relevance
“…The importance of these interferences has been documented by analyzing sera from 47 DTC patients presenting undetectable serum Tg, but residual 131 I uptake on a PT-WBS [33]. This study also pointed to the variability between different Tg immunoassays [33].…”
Section: Does Surgical Pathology Provide Reliable Information For Manmentioning
confidence: 94%
See 1 more Smart Citation
“…The importance of these interferences has been documented by analyzing sera from 47 DTC patients presenting undetectable serum Tg, but residual 131 I uptake on a PT-WBS [33]. This study also pointed to the variability between different Tg immunoassays [33].…”
Section: Does Surgical Pathology Provide Reliable Information For Manmentioning
confidence: 94%
“…Second, interferences by heterophilic antibodies, as well as the so-called Bhigh-dose hook effect,^or decreased immunological reactivity or changes of the structural conformation of the Tg molecule may in rare instances lead to report inappropriately low serum Tg values in sera with high Tg concentrations [32]. The importance of these interferences has been documented by analyzing sera from 47 DTC patients presenting undetectable serum Tg, but residual 131 I uptake on a PT-WBS [33]. This study also pointed to the variability between different Tg immunoassays [33].…”
Section: Does Surgical Pathology Provide Reliable Information For Manmentioning
confidence: 99%
“…In clinical practice, however, patients with clear disease foci or significant thyroid remnants but undetectable serum Tg levels despite a negative TgAb test results are occasionally encountered [52,53]. This may occur when: the spatial conformation of Tg is changed leading to decreased immunoreactivity; the ability to secrete Tg is lost; the TgAb result is a false-negative or inappropriate cut-off values were used.…”
Section: Interferencesmentioning
confidence: 99%
“…The problems of TgAb and HAB interference and the care required in interpretation are exemplified in a recent study 82 of 288 consecutive DTC patients, 47 of whom were found to have an undetectable serum Tg by IMAs but had residual 131 I uptake on post-ablation WBS. To investigate the possibility of antibody interference, the authors measured TgAbs by two different assays, performed Tg recovery experiments, pretreated samples with HAB blocking tubes and measured Tg by two other IMAs.…”
Section: Heterophilic Antibodiesmentioning
confidence: 99%
“…However, given the limitations now noted for TgAb assays themselves, measurement of recovery may aid interpretation in difficult cases. 82 …”
Section: Recovery Of Added Tgmentioning
confidence: 99%